1995
DOI: 10.1002/aoc.590090403
|View full text |Cite
|
Sign up to set email alerts
|

Arsenobetaine and other arsenic species in mushrooms

Abstract: Arsenic species in arsenic-accumulating mushrooms (Sarcosphaera coronaria, Laccaria amethystina, Sarcodon imbricatum, Entoloma lividum, Agaricus haemorrhoidarius, Agaricus placomyces, Lycoperdon perlaturn) were determined. HPLC/ICP MS and ion-exchange chromatography-instrumental neutron activation analysis (NAA) combinations were used. The remarkable accumulator Sarcosphaera coronaria (up to 2000 mg As kg-' dry wt) contained only methylarsonic acid, Entoloma lividum only arsenite and arsenate. In Laccaria amet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 16 publications
5
45
0
Order By: Relevance
“…Only 10% of the extraction yield achieved with orthophosphoric acid and 12% of the extraction yield achieved with water can be reached with methanol/water (9 1). These results correspond to the findings of Byrne et al, 25 who reported higher extraction yields with water than with methanol/water (9 1) in a mushroom sample containing almost all of its arsenic as inorganic arsenic. Almost no differences were observed in the extractability of DMA, the phosphate-, the sulfate-, and the sulfonate-riboses.…”
supporting
confidence: 91%
“…Only 10% of the extraction yield achieved with orthophosphoric acid and 12% of the extraction yield achieved with water can be reached with methanol/water (9 1). These results correspond to the findings of Byrne et al, 25 who reported higher extraction yields with water than with methanol/water (9 1) in a mushroom sample containing almost all of its arsenic as inorganic arsenic. Almost no differences were observed in the extractability of DMA, the phosphate-, the sulfate-, and the sulfonate-riboses.…”
supporting
confidence: 91%
“…Also, the question has arisen as to whether more complex organoantimony species, such as stibiobetaine, might be produced in the environment; other workers have detected arsenobetaine in some arsenic-accumulating terrestrial fungi. 27 It might be worth examining P. schweinitzii to see if such species are present.…”
Section: Discussionmentioning
confidence: 99%
“…These structural types are not present in bacteria and fungi. However, methylarsonate and dimethylarsinate were found in several edible mushrooms (collected in Switzerland and Slovenia) and, as well, arsenobetaine (35). These materials occur in a wide range of terrestrial mushrooms and lichens; other compounds include arsenocholine and the tetramethylarsonium ion (140,145,146,150,220) and small amounts of some arsenoribofuranosides (140).…”
Section: Biomethylation and Bioalkylationmentioning
confidence: 99%